IDENTIFICATION OF CANNABIMIMETIC MDMB(N)-073F METABOLITES IN URINE BY METHOD OF GAS CHROMATOGRAPHY WITH MASS SPECTROMETRIC DETECTION - S. S. Kataev; O. N. Dvorskaya; M. A. Gofenberg (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2019)
Background. At the beginning of 2019, the use of a new representative of synthetic cannabimimetics of the methylbutanoate indazole carboxamides group, MDMB(N)-073F, was recorded in a number of regions in the Russian Federation. Characteristic features of the pharmacological effect, the clinical picture of MDMB(N)-073F poisoning have not been studied, the psychoactive effects produced by MDMB(N)-073F remain unexplored. In this regard, the study of the new cannabimimetic metabolism is an important aspect in establishing the fact of taking MDMB(N)-073F during expert studies of biological objects.The aim of the research is identifying metabolites of synthetic MDMB(N)-73F cannabimimetics in real urine samples using solid-phase extraction (SPE) and gas chromatography (GC) with mass spectrometric detection (GC-MS).Materials and methods. 10 urine samples were collected from March 15 to March 29, 2019. 8 urine samples were taken from the medical examination offices of the city of Yekaterinburg and the Sverdlovsk region from the persons examined for intoxication; 2 urine samples were obtained from the patients of the Sverdlovsk regional center of acute poisoning upon enrolment to the toxic-intensive care unit with a preliminary diagnosis of "acute poisoning by synthetic cannabimimetics". In the research, SampliQ EVIDEX-200 mg - 3 ml (Agilent, USA) cartridges were used for the sample preparation; β-glucuronidase Type HP-2, From Helix Pomatia, 100000 U/ml (Sigma-ALDRICH CHEMI, Germany) was used for enzymatic hydrolysis. Gas chromatography - mass spectrometry with the use of Agilent 7820 gas chromatograph with Agilent 5975 mass selective detector (Agilent, USA) was used as an instrumental method of the analysis.Results. The metabolites that make it possible to establish the fact of taking MDMB(N)-073F cannabimimetics via urine screening procedure to detect the presence of narcotic and medicinal substances with the use of solid-phase extraction and gas chromatography methods with mass spectrometry, have been described. The major metabolites MDMB(N)-073F in the urine of smoking mixtures consumers have been identified. The metabolism of MDMB(N)-073F has been found to be mainly due to hydrolysis of the ester group, hydroxylation, oxidative defluorination and N-dealkylation. Most of the resulting metabolites are excreted in the urine in the conjugated form.Conclusion. Gas chromatographic and mass spectrometric characteristics of some derivatives of the main metabolites of the new synthetic MDMB(N)-073F cannabimimetic have been obtained. This data can be used in the practice of forensic chemical and chemical toxicological analysis.